Developing a Classic Grounded Theory Research Study Protocol - Kara L. Vander Linden; Patrick A. Palmieri (Grounded Theory Review: An International Journal)
The research study protocol is a roadmap for conducting research systematically, efficiently, and ethically. While protocols have standard components, a classic grounded theory protocol differs in its methods, including processes and procedures, because of the uniqueness of the methodology. A classic grounded theory protocol commonly contains the following: (1) introduction to the topic; (2) purpose of the study with the research question; (3) detailed description of the research methods, including data collection and analysis; and (4) procedures to demonstrate the ethical conduct of human participant research. Based on a review of grounded theory methodological literature, the current article describes an approach for developing a research protocol that maintains grounded theory research integrity while adhering to institutional and funding requirements. A properly written study protocol is essential for maintaining methodological fidelity, avoiding method slurring, and unintended remodeling in classic grounded theory.